Modeling and visualization of layered curing conversion profile in ceramic mask projection stereolithography process. Issue 16 (November 2020) - Wu, Xiangquan; Xu, Chunjie; Zhang, Zhongming; Guo, Can
Abstract: Ceramic mask projection stereolithography can be used for printing delicate ceramics through a layer-stacking process. However, the layered printing results in the introduction of layered anisotropy and defects along the layers in the printed parts. An in-depth investigation of the layered properties of curing conversion in the green parts is essential for improving the part quality. In this study, analytical, numerical, and experimental methods were used to characterize the curing conversion of a mask-exposed ceramic slurry. Visualization of the curing conversion profiles was achieved through optical microscopic observation of partially debound green parts. The results showed that the curing conversion in the green body was step-like and non-uniform between and within layers, because of the attenuation of UV light. The largest difference in the curing conversion appeared at the layer bonding interface. Uniform curing conversion should be achieved to reduce the layered properties of printed ceramics.